Pooling of income and sharing of consumption within households. - Bonke, J; Browning, M (Department of Economics (University of Oxford), 2009)
There are extensive literatures within economics and economic psychology on the allocation of household income within the household. These two literatures are largely disjoint but both use a concept of ‘income pooling’. In economics this refers to the independence of household decisions from who receives the income within the household. In economic psychology it refers to the management of household finances. This article uses a new Danish expenditure survey that gives information on both concepts and on the assignment of expenditures to consider the link between the two. More importantly, we investigate whether either type of pooling is related to the sharing of expenditures between the two partners. We find that sharing does depend on who receives the income within non-pooling households, but not on the economic psychological income pooling regime per se.